Q. 53.9( 8 Votes )

# Solve the following quadratic equations by factorization method

x^{2} + x + 1 = 0

Answer :

Given x^{2} + x + 1 = 0

[∵ (a + b)^{2} = a^{2} + 2ab + b^{2}]

We have i^{2} = –1 ⇒ 1 = –i^{2}

By substituting 1 = –i^{2} in the above equation, we get

[∵ a^{2} – b^{2} = (a + b)(a – b)]

Thus, the roots of the given equation are.

Rate this question :

–x^{2} + x – 2 = 0

Solve the following quadratic equations by factorization method:

x^{2} + (1 – 2i)x – 2i = 0

Solve the following quadratics

Solve:

Solve the following quadratic equations by factorization method:

6x^{2} – 17ix – 12 = 0

Solve the following quadratic equations:

x^{2} + 4ix – 4 = 0

Solve the following quadratic equations:

x^{2} – x + (1 + i) = 0

Solve the following quadratic equations:

x^{2} – (2 + i)x – (1 – 7i) = 0

Solve the following quadratic equations:

ix^{2} – x + 12i = 0